Digital society: theoretical outlines of the emerging paradigm - Yu. A. Chernavin (Цифровая социология)
The large-scale changes in the life of modern society caused by digitalization, as well as numerous studies of various manifestations and aspects of this process, give rise to the need to develop a concept of a digital society. The attempt to solve this research problem, implemented in the article, represents one of its possible models.In the proposed model, the digital society is considered as the next stage of post-industrial development and an element of modern global technogenic civilization. The implementation of the plan is based on the institutionalization of digital public relations. The basis of the process is the construct “human – knowledge – communication networks – computer technology”. Its elements in the course of interaction give rise to digital formal and informal institutions in the economy, politics, culture, and social life; form a new structural element of society – the digital information sphere; develop into a whole as a digital society. Digital institutions and the digital sphere, acting as mechanisms for the emergence of society, rely on their own type of activity, have a new type of personality as a subject – “information person”.The analysis, undertaken within the framework of the neo-institutional approach, the features of the socialization of e-Homo Sapiens are revealed, based on the need for presence and activity in the information space, taking into account the impact of modern information technologies, which ultimately contribute to the inconsistency of the emerging typological properties. The decisive role of the human factor in the emergence of the digital society as a knowledge society made it necessary to rely on the principle of social determinism for the entire research structure. This technique allowed us to substantiate the conclusion about the human creator, the subject of social existence as the main characteristic and source of development of the digital society. Any changes in the indicators of subjectivity will serve as factors for the appearance of components of a future civilization based on this society, the contours of which are not transparent today.